PENGARUH KEPEMIMPINAN KEPALA SEKOLAH DAN PERILAKU INOVATIF GURU TERHADAP KINERHA GURU BERSERTIFIKAT PENDIDIK (STUDI PADA SEKOLAH MENENGAH PERTAMA DI KABUPATEN KOTAWARINGIN TIMUR): The Influence of School Principal Leadership and Teachers' Innovative Behavior on the Performance of Certified Teachers (A Study in Junior High Schools in East Kotawaringin Regency) - Muhajir, Muhammad Ikram (Restorica: Jurnal Ilmiah Ilmu Administrasi Negara dan Ilmu Komunikasi, 2024)
Analysis of the Influence of Principal Leadership and Innovative Behavior on the Performance of Certified Educator Teachers (Study at Junior High Schools in East Kotawaringin Regency).This research studies the leadership style of school principals and the innovative behavior of teachers with the aim of determining their influence on teacher performance. The research method was carried out by testing primary data using PLS-SEM tools with a total of 100 respondents spread across East Kotawaringin Regency. The data analysis technique in this research is descriptive statistics and PLS-SEM inner and outer model testing.The results of this research show that the principal's leadership has a p-value of 0.02, which means that leadership has a positive and significant effect on teacher performance. Innovative behavior has a p-value of 0.01, which means innovative behavior has a positive and significant effect on teacher performance. The low R2 value of 14.7% in the research is expected to be able to be tested with other variables outside the research.